Co-circulation of Toscana virus and Punique virus in northern Tunisia: a microneutralisation-based seroprevalence study. - Sonia Sakhria; Laurence Bichaud; Mohamed Mensi; Nicolas Salez; Khalil Dachraoui; Laurence Thirion; Saifedine Cherni; Ifhem Chelbi; Xavier De Lamballerie; Elyes Zhioua; Rémi N Charrel (Public Library of Science (PLoS), 2013)
BACKGROUND: In northern Tunisia, the co-circulation of two related sand fly-borne phleboviruses, Toscana virus (TOSV) and Punique virus (PUNV) was previously demonstrated. In contrast to TOSV, a prominent human pathogen, there is no data supporting that PUNV is capable to infect and cause disease to humans. We studied the respective involvement of TOSV and PUNV in human infections in northern Tunisia through a seroprevalence study. METHODS: The presence of TOSV and PUNV neutralising antibodies (NT-Ab) was tested in human sera collected from 5 districts of the governorate of Bizerte, and the titres of NT-Ab were estimated by microneutralisation (MN) assay. PRINCIPAL FINDINGS: A total of 1,273 sera were processed. TOSV and PUNV NT-Ab were detected in 522 (41%) and 111 sera (8.72%) respectively. TOSV seroprevalence varied from 17.2% to 59.4% depending on the district. Analysis of TOSV geometric mean titre values demonstrated a constant increase according to the age. The vast majority of sera containing NT-Ab were found to be more reactive toward TOSV than PUNV. Indeed, past infections with PUNV and TOSV were undisputable for 5 and 414 sera, respectively. CONCLUSIONS: PUNV may be capable to infect humans but at a low rate. TOSV is responsible for the vast majority of human infections by sand fly-borne phleboviruses in northern Tunisia. TOSV must be considered by physician and tested in diagnostic laboratories for patients with meningitis and unexplained fever in northern Tunisia.